Analisis Literatur ANALISIS LITERATUR: PENERAPAN MODEL GAMES BASED LEARNING BERBASIS DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Nisrina Lutfiyah; Linda Zakiah; Juhana Sakmal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of digital-based Games Based Learning (GBL) model in Indonesian language learning at elementary schools through comprehensive literature review. The research method employs systematic literature analysis by examining various relevant sources from scientific journals, research articles, and academic publications over the past five years. The analysis results indicate that digital-based GBL implementation provides significant positive impacts on Indonesian language learning at elementary level. This learning model successfully creates a more enjoyable and interactive learning atmosphere, increases student learning motivation, and develops critical and creative thinking skills through learning-while-playing experiences. Digital-based GBL proves effective in improving student learning outcomes in aspects of material comprehension, memory retention, and active engagement. The findings indicate that digital technology integration through GBL approach not only addresses monotonous conventional learning but also prepares students to face the digital era.Keywords: Game-Based Learning, Indonesian Language, Digital TechnologyABSTRAKPenelitian ini bertujuan untuk menganalisis penerapan model Games Based Learning (GBL) berbasis digital dalam pembelajaran Bahasa Indonesia di sekolah dasar melalui kajian literatur yang komprehensif. Metode penelitian menggunakan analisis literatur sistematis dengan mengkaji berbagai sumber pustaka relevan dari jurnal ilmiah, artikel penelitian, dan publikasi akademik selama lima tahun terakhir. Hasil analisis menunjukkan bahwa penerapan GBL berbasis digital memberikan dampak positif signifikan terhadap pembelajaran Bahasa Indonesia di tingkat sekolah dasar. Model pembelajaran ini berhasil menciptakan suasana belajar yang lebih menyenangkan dan interaktif, meningkatkan motivasi belajar siswa, serta mengembangkan keterampilan berpikir kritis dan kreatif melalui pengalaman bermain sambil belajar. GBL berbasis digital terbukti efektif meningkatkan hasil belajar siswa dalam aspek pemahaman materi, daya ingat, dan keterlibatan aktif. Temuan mengindikasikan bahwa integrasi teknologi digital melalui pendekatan GBL tidak hanya mengatasi pembelajaran konvensional yang monoton, tetapi juga mempersiapkan siswa menghadapi era digital.